Departure from the vogel behaviour in the glass transition region-thermally stimulated recovery, creep and dynamic mechanical analysis studies - Alves, N. M. (2004)
In this work the study of the dynamics of the segmental motions close to Tg of a poly(methyl methacrylate), PMMA, network was analysed by distinct mechanical spectroscopy techniques. Three techniques were employed: dynamic mechanical analysis (DMA), creep and thermally stimulated recovery (TSR). The time–temperature superposition principle was applied to the DMA and creep results, and master curves were successfully constructed. A change from a Vogel to an Arrhenius behaviour was observed in these results. Above Tg it was found a distinct temperature dependence for the retardation times calculated from creep and the relaxation times calculated from DMA. This unexpected behaviour was attributed to the merging of the a and the b relaxations that occurs in PMMA systems. The apparent activation energies ðEaÞ were also calculated from DMA, creep and TSR experiments. Above Tg the Ea values obtained agreed very well for all the techniques. In addition, the fragility exhibited by this material was investigated by the mechanical spectroscopy techniques referred above and by differential scanning calorimetry (DSC). The obtained values of the fragility index m indicated that the PMMA network is a kinetically fragile system. The thermodynamic manifestation of the fragility was also analysed.